Characterization of drug resistant Salmonella enterica Serotype Typhimurium by Antibiograms, Plasmids, Integrons, Resistance Genes and PFGE - Benacer, Douadi; Thong, Kwai Lin; Watanabe, Haruo; Puthucheary, Savithri Devi (The Korean Society for Applied Microbiology, 2010)
Forty-seven Salmonella Typhimurium (33 zoonotic, 14 clinical) strains were tested for antimicrobial resistance using the standard disk diffusion method. The presence of relevant resistance genes and class 1 integrons were investigated by using PCR. Pulsed-field gel electrophoresis (PFGE) and plasmid profiling were carried out to determine the genomic diversity of Salmonella Typhimurium. Approximately 57.4 of the S. Typhimurium strains were multidrug resistant (MDR) and showed high resistance rates to tetracycline (70.2), sulfonamides (57.4), streptomycin (53.1), ampicillin (29.7), nalidixic acid (27.6), kanamycin (23.4), chloramphenicol (21.2), and trimethoprim (19.1). Resistance towards cephalosporins was noted for cephalothin (27.6), cephradine (21.2), amoxicillin clavulanic acid (17.0), and cephalexin (17.0). Resistance genes, bla(TEM), strA, aadA, sul1, sul2, tetA, tetB, and tetC, were detected among the drug-resistant strains. Thirty-three strains (70.2) carried class 1 integrons, which were grouped in 9 different profiles. DNA sequencing identified sat, aadA, pse-1, and dfrA genes in variable regions on class 1 integrons. Thirty-five strains (74.4) were subtyped to 22 different plasmid profiles, each with 1-6 plasmids (2.0 to 95 kb). PFGE subtyped the 47 strains into 39 profiles. In conclusion, high rates of multidrug resistance were found among the Malaysian Salmonella Typhimurium strains. The emergence of multidrug-resistant Salmonella Typhimurium to cephalosporin antibiotics was also observed. The strains were very diverse and no persistent clone was observed. The emergence of MDR Salmonella Typhimurium is a worldwide problem, and this report provides information for the better understanding of the prevalence and epidemiology of MDR S. Typhimurium in Malaysia.